Case Report Effectiveness of Using Antibiotics as Infection Prevention in Open Pneumothorax: Post Chest Tube: Effectiveness of Using Antibiotics as Infection Prevention in Open Pneumothorax: Post Chest Tube, Case Report - Made Jayawisesa Priyambhada Putra; Muhammad teguh hadinata; Made Sopan Pradnya Nirartha (Faculty of Medicine, Universitas Mataram, 2022)
BACKGROUND: Open pneumothorax is an injury caused by sharp trauma or blunt, causing the thoracic cavity to open and air can enter from the outside. Open pneumothorax is a potentially lethal illness that requires cautious early management and the mortality rate was found to be 33%. In general, a chest tube is used to establish the negative pressure in the thorax cavity and facilitate redevelopment of the pulmo to assist remove air from the intrathoracic space. Antibiotics are usually given to prevent infection in the patient. We will report a case related to the effectiveness of using antibiotics as infection prevention in open pneumothorax post chest tube. CASE REPORT: We report a case of a 20-year-old man that was presented to our emergency department after got a traffic accident. The patient complained of chest pain, shortness of breath, and no other complaints. The patient was found to have an open wound on the right chest, measuring 5 x 3 cm with a lung wound base, and active bleeding. The patient's chest was found to be hyper resonant, decreased vesicular breath sounds, and asymmetry in physical examination. The patient was diagnosed with open pneumothorax and further instruction was surgical disposition. There were no radiological abnormalities on the chest x-ray of this patient. The main therapy, in this case, was the administration of antibiotics and the installation of a chest tube. The patient experienced postoperative pain after the insertion of a chest tube. Complete blood counts showed relatively normal results after three days and the patient stated that his complaints had decreased after four days. Two weeks later, the patient's previous complaints had not been felt. This condition indicates that there is no infection in the patient that can be associated with the administration of antibiotics. The therapy process is continued with chest physiotherapy until ten weeks later. CONCLUSION: The administration of antibiotics to this patient with open pneumothorax post chest tube indicated an effective result. Further research is needed to support the existing literature sources regarding open pneumothorax.